Pengaruh Jenis Mordan Dan Lama Waktu Pencelupan Terhadap Kualitas Warna Kain Batik Dengan Pewarnaan Alam Kulit Bawang Merah Menggunakan Proses Post-Mordanting - Rizky Bellyana Noermitha; Malik Musthofa; Agus Haerudin (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Red onion skin is one of the wastes that can be used as a natural dye because it contains anthocyanins which are one of the natural color pigments. The availability of red onion skin waste is very abundant, especially from household waste and industrial waste which has not been optimally utilized. The purpose of this study was to determine the effect of fixation type with different dyeing times on the color quality of batik fabric. This research method is an experiment by varying the fabric treatment in the pre-mordanting process, time variations of 30 and 60 minutes, and fixation variations, namely alum, arbor, and quicklime. The results of the study obtained that red onion skin extract is very good as a natural dye for dyeing batik fabric, the value of the color fastness test at 40 ℃ soap washing and cloth rubbing (wet) shows good quality with an average value of 4 and 4 - 5. The value of the L *, a *, b * color difference test and the results of visual observations on the pantone color produce an orange-red color that contains dominant color elements towards reddish and yellowish.